Ответ:
Объяснение:
Есть такие формулы:
sin^2 a + cos^2 a = 1
1 + tg^2 a = 1/cos^2 a
1 + ctg^2 a = 1/sin^2 a
Подставляем их в наши выражения и получаем:
1)
2)
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
Объяснение:
Есть такие формулы:
sin^2 a + cos^2 a = 1
1 + tg^2 a = 1/cos^2 a
1 + ctg^2 a = 1/sin^2 a
Подставляем их в наши выражения и получаем:
1)![\frac{1}{\sqrt{1-cos^2(a)} } +\sqrt{1+ctg^2(a)} = \frac{1}{sin(a)} +\frac{1}{sin(a)} =\frac{2}{sin(a)} \frac{1}{\sqrt{1-cos^2(a)} } +\sqrt{1+ctg^2(a)} = \frac{1}{sin(a)} +\frac{1}{sin(a)} =\frac{2}{sin(a)}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B%5Csqrt%7B1-cos%5E2%28a%29%7D%20%7D%20%2B%5Csqrt%7B1%2Bctg%5E2%28a%29%7D%20%3D%20%5Cfrac%7B1%7D%7Bsin%28a%29%7D%20%2B%5Cfrac%7B1%7D%7Bsin%28a%29%7D%20%3D%5Cfrac%7B2%7D%7Bsin%28a%29%7D)
2)![\frac{1}{\sqrt{1+tg^2(a)} } +\sqrt{1-sin^2(a)} =cos(a)+cos(a)=2cos(a) \frac{1}{\sqrt{1+tg^2(a)} } +\sqrt{1-sin^2(a)} =cos(a)+cos(a)=2cos(a)](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B%5Csqrt%7B1%2Btg%5E2%28a%29%7D%20%7D%20%2B%5Csqrt%7B1-sin%5E2%28a%29%7D%20%3Dcos%28a%29%2Bcos%28a%29%3D2cos%28a%29)